Effect of intercropping oilseed and pulse crops in upland cotton (Gossypium hirsutum) for total productivity and monetary advantage in the system - Sarkar, R K; Chakraborty, A; Majumdar, R C (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during 1990-91 and 1991-92 to study the effect of inter cropping oilseed crops [sesame (Sesamum indicum L.), linseed (Linum usitatissimum L.) and groundnut (Arachis hypogaea L.)] and a pulse crop [greengram (phaseolus radiatus L.)] in upland cotton (Gossypium hirsutum L.) for information on total productivity and monetary advantage in the system. Intercropping of 2 rows of greengram in paired-row planted upland cotton gave higher cotton-equivalent yield (2 40B kg/ha) and monetary advantage (Rs 6 143/ha) than sole cropping of upland cotton (1 393 kg/ha).